VISUALISASI HASIL PAJAK BUMI BANGUNAN BERBASIS WEBGIS 3D - Ardiansyah, Andre; Yulfa, Arie (JURNAL BUANA, 2026)
WebGIS 3D is a geographic information system that allows users to view, analyze, and interact with geospatial data in three-dimensional format via the web. This WebGIS utilizes 3D mapping technology to provide deeper visualization, allowing users to explore location information with a more realistic perspective, such as in urban planning, environmental analysis, and infrastructure development. The results of the 3D-based webGIS of the Koto Baru Nagari building, WebGIS from Koto Baru Nagari can display information about the type of building to the PPB value of a building in the area. LiDAR Data Processing using DJITerra Software. LiDAR (Light Detection and Ranging) is a remote sensing technology that uses light in the form of a laser to measure the distance of an object or surface. LiDAR Data Processing using DJITerra. LiDAR Data Processing using TerraSolid New Drone Project. Drone Data Processing In the Wizard, select Drone Data Processing, activate the processing Step you want to apply. At each processing Step, click the settings button to check and adjust the settings.Keywords: Webgis, Tax, Webgis 3D, Building